Consumption: Ethical Perspective of Islamic Economics - Yana Rohmana (Review of Islamic Economics and Finance, 2022)
AbstractPurpose – The problem of consumption in the framework of Islamic economics is how to fulfill needs so that satisfaction is achieved, full of ethics by adding social preferences and benefits, and hoping to achieve the pleasure of Allah SWT.Methodology - Such consumer behavior should be based on Islamic moral consumption ethics with the guidelines of the Qur'an and Sunnah. The principles of consumption within the framework of Islamic ethics, namely (i) the principle of permissibility and generosity; (ii) Responsibility and Simplicity Principles; (iii) Principles of Balance and Fairness; and (iv) Priority and Morality Principles.Findings - All consumption ethics are aimed at achieving falah, which is a noble and prosperous life in this world and the hereafter with the fulfillment of the needs of human life in a balanced way. The fulfillment of community needs will have an impact called mashlahah (individual and social welfare) in the hope of achieving the pleasure of Allah SWT. So it is fitting that the consumption of a Muslim is as a means of help to worship Allah SWT. So its consumption must conform to the hierarchy of essential (darūriyyāt), complementary (hājiyyāt) and embellished (taḥsīniyyāt) needs. Islam forbids consumers to take extreme actions (up to the upper limit) in the form of excessive consumption (israf) or wasteful consumption (tabdhir), and also avoid stingy consumption. The prohibition set is not to limit mankind, but to ensure the benefits are maintained and harm is avoided in consumption.Keywords: Consumption, Ethics, Islam, Falah